OXYGEN-CONTAINING SUBUNITS IN SULFUR-RICH NONPOLAR MACROMOLECULES - IMPLICATIONS FOR STUDIES OF PALEOCLIMATE - Jenisch-Anton A.; Adam P.; Schaeffer P.; Albrecht P. (My University, 1999)
Substantial amounts of alcohols occur in the desulfurization products of sulfur-rich nonpolar macromolecular fractions (NPMF) isolated from two crude oils and a sediment extract. These macromolecularly bound oxygenated compounds have been investigated in detail. Released straight chain components may have a hydroxy functionality at any position of the carbon skeleton and without any isomer predominance. Furthermore, the carbon-number distributions are very similar for the different alcohol isomers in each case and resemble those of the aliphatic hydrocarbons released by desulfurization. Thus, released hydrocarbons and alcohols likely originate from common functionalized precursors, most probably from polyunsaturated lipids of biological origin. Furthermore, they may derive from polyunsaturated components formed by elimination reactions on functionalized precursors which incorporated oxygen in free or already bound form at an early stage of diagenesis. The presence of hydroxyl functionalities at every position in the carbon skeleton suggests that double bond isomerization probably occurred in linear components prior to oxygen incorporation. Similarly, 2-hydroxy stanols released by desulfurization most likely result from oxygen uptake into Δ2-sterenes during diagenesis. The presence of mid-chain hydroxylated phytanols in the degradation products with OH-group mainly at the tertiary positions indicates that they result (at least partially) from oxygen incorporation into unsaturated phytane skeletons. Additional functionalities in the oxygenated substances, such as double bonds, aldehydes or allylic alcohols, may have served as substrates for reactions with sulfur species, resulting in sulfur-rich cross-linked macromolecular structures.The type of oxygen groups present in the macromolecules could be partially assigned by sequential chemical degradation experiments. The results indicate that free OH-functions are not abundant. Part of the oxygen is present as carboxylic acid, ester and ketone functions. However, the nature of a substantial part of the oxygen species remains unclear.